A visual introduction to wild cats - Stonehouse, Bernard; Orr, Richard (New York : Checkmark Books, 1999)
Introduces the different kinds of wild cats, their physical characteristics, behavior, habitats, and relationship with humans.
Includes index.
Keywords: Felidae -- Juvenile literature; Cat family (Mammals); Cats